2020
DOI: 10.1002/ejp.1651
|View full text |Cite
|
Sign up to set email alerts
|

The burden of pain in rheumatoid arthritis: Impact of disease activity and psychological factors

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…Our study also revealed that participation in social activities by patients with RA and SpA was negatively associated with inflammatory activity, as measured using DAS28 and BASDAI, respectively. This finding is consistent with those of other studies of RA, which found an association between increased inflammatory activity and pain, anxiety, depression, and quality of life [ 33 ]. In SpA, inflammatory activity measured using the BASDAI was also associated with greater depression, anxiety, and sleep disorders [ 3 ]; therefore, control of inflammation could improve these psychological factors, even participation in social activities.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also revealed that participation in social activities by patients with RA and SpA was negatively associated with inflammatory activity, as measured using DAS28 and BASDAI, respectively. This finding is consistent with those of other studies of RA, which found an association between increased inflammatory activity and pain, anxiety, depression, and quality of life [ 33 ]. In SpA, inflammatory activity measured using the BASDAI was also associated with greater depression, anxiety, and sleep disorders [ 3 ]; therefore, control of inflammation could improve these psychological factors, even participation in social activities.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we aimed to evaluate the impact of depression and anxiety assessed with STAI and BDI questionnaires on periodontal treatment outcomes. The French versions of STAI and BDI were selected due to their strong validation, reliability, internal consistency and extensive use in order to evaluate the association between psychological status and chronic diseases [38][39][40][41]. In a previous analysis where depression level was measured using the depression score of the DASS-42 self-administered questionnaire, an association between depression and worsened SRP outcomes was observed, especially regarding the evolution of BOP and reduction in deep sites with PPD > 5 mm and >7 mm [20].…”
Section: Discussionmentioning
confidence: 99%
“…Joint pain is a cardinal clinical feature of RA that significantly impacts quality of life 2 . Although RA pain is often thought to be of inflammatory origin, pain outcomes in RA can be poor despite optimal control of inflammation with current biologic therapies 3 . Therefore, new targeted therapies to effectively manage RA pain are urgently needed.…”
Section: Introductionmentioning
confidence: 99%